Venous Thromboembolism Chemoprophylaxis in Burn Patients: A Literature Review and Single-Institution Experience. Issue 1 (3rd January 2021) - Liu, Alice; Minasian, Raquel A; Maniago, Ellen; Justin Gillenwater, T; Garner, Warren L; Yenikomshian, Haig A
Abstract: Hospitalized burn patients meet the criteria for Virchow's triad (endothelial damage, hypercoagulability, and stasis), predisposing them to venous thromboembolism (VTE). Although the disease burden of VTE suggests a need for prevention in this population, unreliable reported VTE rates, costly and complicated prophylaxis regimens, and chemoprophylaxis risks have prevented the establishment of a universal protocol. This paper reviews thromboprophylaxis practices both in the literature and at our own institution. A systematic review was conducted according to PRISMA guidelines identifying studies pertaining to VTE chemoprophylaxis in burn patients. Additionally, medical records of patients admitted to an American Burn Association-verified burn center between June 2015 and June 2019 were retrospectively reviewed for demographics, chemoprophylaxis, and presence of VTE defined as either deep vein thrombosis (DVT) or pulmonary embolism (PE). Thirty-eight studies met inclusion criteria. In the 12 studies that reported VTE incidence, rates ranged widely from 0.25% to 47.1%. The two largest retrospective studies (n = 33, 637 and 36, 638) reported a VTE incidence of 0.61% and 0.8% in populations with unknown or inconsistently recorded chemoprophylaxis. Throughout the literature, prevention protocols were mixed, though a trend toward using dose-adjusted subcutaneous low molecular weight heparin based on serum anti-factor Xa level was noted. At our burn center, 1, 068 patients met study criteria. At-risk patients received a simple chemoprophylaxis regimen of 5000U of subcutaneous unfractionated heparin every 8 hours. No routine monitoring tests were performed to limit cost. Nine cases of DVT and two cases of PE were identified with an incidence of 0.84% and 0.19%, respectively, and a total VTE incidence of 1.03%. Only one patient developed heparin-induced thrombocytopenia (HIT). No cases of other heparin-associated complications were observed. VTE incidence rates reported in the literature are wide-ranging and poorly capture the effect of any one chemoprophylaxis regimen in the burn population. Our center uses a single, safe, and cost-effective protocol effecting a low VTE rate comparable to that of large national retrospective studies.